2001
DOI: 10.1007/s007050170125
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of Alfalfa mosaic virus RNA 3 into an expression vector

Abstract: RNA 3 of alfalfa mosaic virus (AMV) encodes the 5'-proximal movement protein (MP) gene and the 3'-proximal coat protein (CP) gene which is expressed from a subgenomic RNA. Several strategies were explored to use this RNA as a vector for expression of the green fluorescent protein (GFP) in Nicotiana tabaccum plants expressing the viral polymerase proteins P1 and P2 (P12 plants). Insertion of a subgenomic promoter (sgp)-GFP cassette between the CP gene and the 3'-untranslated region (UTR) interfered with RNA acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
5

Year Published

2002
2002
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 34 publications
0
50
0
5
Order By: Relevance
“…Newly synthesized mRNAs egress into the cytoplasm for sgRNA transcription (f) and translation of other viral products, such as MP and CP, that are engaged in virion maturation (g). The presence of viral MP triggers the formation of tubular structures that mediate virion cell-to-cell transfer via a tubule-guided mechanism (99,109,134). ER, endoplasmic reticulum.…”
Section: Rna Replicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Newly synthesized mRNAs egress into the cytoplasm for sgRNA transcription (f) and translation of other viral products, such as MP and CP, that are engaged in virion maturation (g). The presence of viral MP triggers the formation of tubular structures that mediate virion cell-to-cell transfer via a tubule-guided mechanism (99,109,134). ER, endoplasmic reticulum.…”
Section: Rna Replicationmentioning
confidence: 99%
“…These structures were shown to traverse the cell wall through modified plasmodesmata, and they mediate virion transfer via a tubule-guided mechanism (13,41,99,109,134). Recent studies performed with N. benthamiana plants and protoplasts have shown that host factors were engaged in the regulation of the BMV MP localization to the plasmodesmata (50).…”
Section: Virus Movementmentioning
confidence: 99%
“…However, an additional number of other promising virus vectors have recently been described. Relatively new or improved additions to the repertoire of viral gene vectors are represented by Tobacco rattle virus (TRV) (13), Wheat streak mosaic virus (WSMV) (24), Tomato bushy stunt virus (TBSV) (2,9,20,25,26), Plum pox virus (PPV) (27), Zucchini yellow mosaic virus (28), Cucumber mosaic virus (29), White clover mosaic virus (18), Clover yellow vein virus (30), Alfalfa mosaic virus (ALMV) (3,19), and Cowpea mosaic virus (CPMV) (4,. 8, 10, 31).…”
Section: Construction Methodologymentioning
confidence: 99%
“…In the complementation approach, a foreign gene is used to replace an essential virus gene. The displaced gene is complemented by a tunctionally analogous gene that is expressed from a co-inoculated viral or subviral component, or from a trans gene (18,19).Most virus vectors are based on viruses that initially were selected as subjects of study because they caused economically impoliant disease problems. In many cases the struggle to combat these viruses continues.…”
mentioning
confidence: 99%
“…N. tabacum wild-type, P1, P2, or P12 plants were inoculated with a mixture of capped transcripts corresponding to AMV RNA1 and RNA2, a modified RNA3 that expresses the green fluorescent protein (GFP) (25), and a few micrograms of purified AMV coat protein as described in reference 26. The fluorescence derived from chimeric AMV RNA3 encoding GFP was monitored with a Leica stereoscopic microscope.…”
Section: Dose-response Experimentsmentioning
confidence: 99%